The reinforcing effects and mechanisms of multi-layer graphenes on mechanical properties of reactive powder concrete. (10th August 2020) - Li, Linwei; Zheng, Qiaofeng; Dong, Sufen; Wang, Xinyue; Han, Baoguo
Highlights: Multi-layer graphene (MLG) were used to reinforce reactive powder concrete (RPC). Reinforcing mechanism of MLG to RPC was investigated through electrical properties. Compressive strength and pore solution resistance were negatively correlated. Adding MLG can fill pores, reduce pore size and reduce weakened area in RPC. Incorporating MLG can reduce CaO/SiO2 ratio of C-S-H gel and size of CH crystal. Abstract: The utilization of multi-layer graphenes (MLGs) as reinforcement for reactive powder concrete (RPC) is motivated by their flat morphology, unique stacking structure, high stiffness/strength, and high electron mobility. This paper studied compressive strength, flexural strength and flexural stress-strain relationship of MLGs reinforced RPC (MRRPC). Electrical properties including electrical resistivity and electrochemical impedance spectroscopy were tested to characterize RPC's pore structure firstly. Besides, the microstructure of MRRPC was observed using scanning electron microscope, and CaO/SiO2 ratio of C-S-H gel was obtained by energy dispersive spectrometer. The results show that the MRRPC filled with 0.5 wt% MLGs exhibits maximum compressive strength of 123.2 MPa. MRRPC filled with 0.75 wt% MLGs presents maximum flexural strength of 11.08 MPa, along with 18.7% enhancement to ultimate flexural strain. Electrical properties' results suggest pore structure of RPC can be modified by MLGs. Negative correlation between compressive strength and two electrical parameters including electrical resistivity increase and pore solution resistance is observed. Moreover, CaO/SiO2 ratio of C-S-H gel is decreased and size of calcium hydroxide crystal is reduced along with the addition of MLGs, implying MLGs can fill pores and reduce weakened areas in RPC matrix effectively.